نموذج تشكيل كراسي الطلاب المفرح في تعزيز حفز التعلم - Anita Andriya Ningsih (Lugawiyyat, 2020)
In the process of learning teaching the most important aspects of it is classroom management. Classroom management must be mastered by teachers in a theoretical and practical way. Teachers should understand how to organize and utilize all the facilities and infrastructure in the learning process to learn effectively and in fun. Sitting formation Setup is one of the most enjoyable and effective class management components because it can involve all students and teachers more able to know and understand the ability of pupils with all the advantages and disadvantages. Various seating models with all advantages and disadvantages can be tested to maximize the utilization of school facilities and infrastructure and motivate students in the teaching and learning process.